Desenvolvimento de língua adicional (alemão) na educação infantil: processo de imersão em aulas de experimentação científica - Siqueira, Carla Ahlemeyer (2020)
This research has the general objective of analysing and understanding how children from a kindergarten class develop the German language in an immersion process, in moments of scientific experimentation. The school in which the study is carried out is part of the universe of elite schools of Bilingual Education (LIBERALI; MEGALE, 2016; MARCELINO, 2009; MEGALE, 2005, 2018) and works with immersion in the german language (JOHNSON, 1997; GARCIA, 2009). In this context, the focus of this research is in the discipline of Nature and Society. Theoretically it is supported by the Historical-Cultural Theory, based on the discussions of Vygotsky ([1930]1991, [1934]2002), particularly regarding the concepts of Language, Mediation and Zone of Proximal Development. In this conception, language is central and proposes to expand the linguistic repertoire of the participants and to analyze translingual practices (GARCIA, 2009; GARCIA; BARTLETT; KLEIFGEN, 2006; GARCIA; LIN, 2016). These research questions are: 1. How is the cycle of scientific research organized through dimensions of questions? 2. What resources do children use to interact with the teachers, the researcher and colleagues? What do they reveal about the development of an additional language? Methodologically, this research was organized based on the Critical Collaboration Research (MAGALHÃES, 2012; NININ, MAGALHÃES, 2017), which proposes to create collaborative relationships in the production of critical knowledge in school practices. 24 six year old children, one educator and the researcher participated in this sutdy. The data was produced in a classroom, collected through video recordings and transcribed for analysis. The participation of the ones involved in the experimentation process was analysed from the enunciative, discursive and linguistic levels, the dimensions of questions and translingual practices. The results revealed that in the cycle of scientific research, dimensions of questions were focused that encouraged the development of the additional language, and the teacher's acceptance of translational practices in the process was central